Adaptif Petani Terhadap Program Kartu Tani di Kecamatan Purwodadi Kabupaten Purworejo - Dullah, Intan C (Universitas Muhammadiyah Semarang, 2022)
The scarcity of subsidized fertilizers occurs because the need for fertilizer is high while the availability at the retailer/seller level is low, resulting in increasing fertilizer prices. Efforts to overcome problems related to subsidized fertilizers are through the Kartu Tani program. The Tani Card is used as a means of redemption and payment for subsidized fertilizers. This study aims to examine the characteristics of respondents (internal factors and external factors) recipients of the farmer card program, examine the response of farmers to the implementation of the farmer card program and examine the effect of respondent characteristics on farmer responses to the implementation of the farmer card program. The research location was determined purposively in Purwodadi District, Purworejo Regency. The consideration for choosing the location is that Purworejo Regency is the Regency with the largest rice harvest area in Purworejo Regency. The sampling method was proportional random sampling with a sample size of 60 farmers. Data analysis used multiple linear regression. The results showed that the response of most farmers to the Kartu Tani program from the cognitive aspect was high, from the affective aspect it was high, from the conative aspect it was high, and from the behavioral aspect it was high.